Factors contributing to neonatal mortality in a tertiary center in south West Bank: A single-center retrospective cohort study. - Ahmad Abu Sharkh; Farah Ighneimat; Yazan F Khdour; Noor Y Aladam; Inad Nawajaa; Alaa Al Janazerah; Insaf Najajrah; Beesan Maraqa (PLOS Global Public Health, 2025)
Neonatal mortality remains a critical public health issue, particularly in low- and middle-income countries, where factors such as preterm birth, low birth weight, congenital anomalies, infections, and limited access to quality healthcare contribute significantly to neonatal deaths. This study examines neonatal mortality outcomes in the Neonatal Intensive Care Unit (NICU) at the Palestine Red Crescent Society (PRCS) Hospital in Hebron, Palestine for newborns that was transferred to PRCS from other hospitals. An institutional-based cohort study was conducted on 606 neonates admitted "transferred from other hospitals" to the NICU at PRCS Hospital from 2019 to 2024. Data were collected from the hospital's electronic registry, capturing clinical parameters and potential risk factors. Statistical analysis, including bivariate and multivariable logistic regressions, was performed using SPSS version 25 to evaluate neonatal mortality risk variables. Of the 606 neonates admitted "transferred from other hospitals" to the NICU over five years, 21.5% died, reflecting a substantial neonatal mortality rate. The study identified significant associations between neonatal mortality and sepsis (p = 0.001, aOR=2.34), intraventricular hemorrhage (p < 0.001, aOR=4.67), and necrotizing enterocolitis (p = 0.001, aOR=3.58). Transfer process, Sepsis, intraventricular hemorrhage, necrotizing enterocolitis, prematurity, low birth weight, and hypothermia were key factors associated with neonatal mortality in this NICU setting. Prioritizing early management of sepsis, NEC, and low birth weight is crucial to reducing neonatal deaths in institutional settings. These findings can guide interventions to improve neonatal outcomes and support healthcare facilities in transfer process training for high-risk newborns to reduce preventable deaths.